Safety and efficacy of ivermectin in times of COVID-19 - Luque Espino, Julio César (2021)
Since its appearance in December 2019, the SARS-CoV-2 infection spread rapidly to the whole world. About 80 % of COVID-19 patients have mild to moderate symptoms, 20 % develop severe respiratory symptoms, and about 6 % may require mechanical ventilation. In the absence of clinically proven treatment guidelines, several well-known drugs began to be evaluated in clinical trials for their likely benefits in the treatment of COVID-19. Among them is the antiparasitic drug ivermectin, one of the avermactins produced by the bacterium Streptomyces avermitilis, discovered in the seventies by Professor Omura's group in collaboration with the pharmaceutical industry. Ivermectin has been shown to inhibit the interaction between viral protein and importin α/β1 heterodimer, leading to inhibition of viral replication. This mechanism of action of ivermectin against SARS-CoV-2 was recently demonstrated in Vero/hSLAM cells. To date, theresults of a clinical trial conducted in Argentina that prove the usefulness of ivermectin in the early stages of the disease are known. In addition, around 40 clinical studies, which seek to confirm the importance of ivermectin as a cost-effective treatment for COVID-19, are registered worldwide. Regarding its safety, ivermectin has proven to be a well-tolerated drug over the years.